Methane/Air Auto-Ignition Based on Global Quasi-Linearization (GQL) and Directed Relation Graph (DRG): Implementation and Comparison. Issue 9 (1st September 2020) - Yu, Chunkan; Minuzzi, Felipe; Bykov, Viatcheslav; Maas, Ulrich
ABSTRACT: In this work, two different reduction methods for simplification of chemical kinetics, the Global Quasi-linearization (GQL) and the Directed Relation Graph (DRG), are implemented and compared for ignition of CH   4 /air homogeneous reacting system. The GQL approach is an automatic and scaling invariant method for a global analysis of the combustion system time-scale hierarchy that takes into account all the original species and elementary reactions, while the DRG is a reduction method for construction of skeletal mechanism that aims at removing unimportant species and thus elementary reactions from the original detailed kinetics. The auto-ignition process is used for validation in a wide range of system parameters and initial conditions which are important for gas turbines, dual-fuel diesel engines, etc. The present study shows that for methane combustion system studied in this work DRG requires dimensions at least two times higher than GQL to ensure the same level of accuracy for the whole range of considered system parameters. And, the advantages and disadvantages of both methods are discussed.